(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This study aimed to determine the relationship between self-confidence, perceived problem-solving skills, and academic performance in Mathematics among Grade 7 students at Basak National High School, Mandaue City, for the school year 2024–2025. Employing a descriptive-correlational research design, the study utilized total enumeration, involving all 296 Grade 7 students as respondents. Data were collected through a validated questionnaire adapted from Fennema-Sherman (for self-confidence) and Erdem-Keklik (for problem-solving skills), while academic performance was based on third-quarter Mathematics grades. Statistical tools included frequency, percentage, weighted mean, standard deviation, and Pearson Product-Moment Correlation Coefficient. Results revealed that students had a moderate level of self-confidence (WM = 3.17), moderate perceived problem-solving skills (WM = 3.29), and a satisfactory level of academic performance (mean grade = 83.69). A strong positive correlation was found between self-confidence and problem-solving skills (r = 0.757, p < 0.05). However, only negligible but significant correlations existed between self-confidence and academic performance (r = 0.202), and problem-solving skills and academic performance (r = 0.245). The study concludes that while self-confidence significantly influences students’ perceived problem-solving abilities, its impact on actual academic performance is limited. It recommends that Mathematics instruction include affective support strategies—such as feedback, modeling, and scaffolding—to enhance both confidence and cognitive skills. An action plan was proposed to improve students’ mathematical engagement and outcomes.